Διαγλωσσικότητα και ταυτότητα: friend or gharīb? - Τσοκαλίδου Luolan (罗兰 ) Ρούλα (Παιδαγωγικά ρεύματα στο Αιγαίο, 2024)
This paper, titled “Translanguaging and identity: friend or gharīb”, is based on the experiences and challenges of some of the participants in my 2017 research, which led to the book SiDaYes: beyond bilingualism to translanguaging. Here I will attempt to highlight some aspects of being translingual, which I believe can be of interest and will most likely continue to concern us in the future, within the wider field of language and culture contact. Identity issues seem to be core issues within the area of translanguaging, both at an individual and a social level. One of the central notions that is discussed is that of being a ‘gharīb’, or an outsider, which seems to have negative and possible positive aspects, according to the individual experience and the overall context in which languages form a linguistic universe of translanguaging experience. 换句话说，多语言实践不断挑战我们对自我、身份的认知。我们研究这一领域的人需要不断寻求理解身份认同问题的新方法[i]。